2016
DOI: 10.17987/icfj.v5i0.239
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Takotsubo Cardiomyopathy

Abstract: IntroductionTakotsubo cardiomyopathy (TC) is transient systolic dysfunction of the left ventricle (LV) occurring mainly in post-menopausal women after a stressful event. It is associated with characteristic LV contraction patterns, typically apical dyskinesia and basal hyperkinesia. 1 The exact pathophysiology of TC is still unclear, although several hypotheses, such as multivessel coronary spasm, microvascular impairment, and direct catecholaminemediated myocardial stunning, have been proposed.2 While the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Emerging evidence indicates that Takotsubo is a syndrome with a significant risk of recurrence (Kato, Kitahara & Kobayashi, 2016;Singh et al 2014) and lingering symptoms that can severely impair QoL. As observed by Dahlviken et al (2015), women with TS require education and counselling from healthcare professionals to help them to comprehend and manage having a TS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that Takotsubo is a syndrome with a significant risk of recurrence (Kato, Kitahara & Kobayashi, 2016;Singh et al 2014) and lingering symptoms that can severely impair QoL. As observed by Dahlviken et al (2015), women with TS require education and counselling from healthcare professionals to help them to comprehend and manage having a TS diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 31 studies involving 1664 patients, Singh et al 55 reported a cumulative recurrence rate of 5% at 6 years with an annual rate of 1.5%. Kato et al 56 in a recent meta-analysis of 3513 patients, recurrence rate was varying 0–10% in the 16 studies. Factors predictive of recurrence were severe LV dysfunction, increased susceptibility to emotion or physical stress, dynamic variation in the sensitivity of cardiac adrenergic receptors and females under 50 years.…”
Section: Prevention Of Recurrences By Drugsmentioning
confidence: 99%
“…Left ventricular dysfunction usually resolves over days to weeks, but in patients who have persistent HFrEF, medical therapy for heart failure should be offered. The incidence of recurrence is not well defined but may be up to 10% (Kato et al., 2016). All patients should have initial follow-up in secondary care.…”
Section: Unclassifiedmentioning
confidence: 99%